2022
DOI: 10.1002/cae.22554
|View full text |Cite
|
Sign up to set email alerts
|

What topics should or should not be included in software security education—Qualitative content analysis

Abstract: Software security education is still not preparing students for the types of high‐skilled technical roles that represent the most severe workforce shortage. Recognizing this, academia has begun redefining the knowledge area concepts of software security curricula to meet the current workforce shortage. This article studies the software security courses in Arab Gulf academic programs and benchmarks their descriptions with the corresponding knowledge area from cybersecurity Curricula (CSEC). 2017, the first set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In India, the study by Rathod [22] indicated a practical need to heighten personal cybersecurity among higher-education students who constantly use distance education through the diversity of cyber-hygiene knowledge, awareness, and behaviours. In UAE, implementing the approaches of cyber-hygiene awareness concern applied as a holistic approach in higher education is critical to affecting online learning practices amid COVID-19 [40]. Other articles from the Arab Region empirically examined cyber-hygiene culture and awareness among students in higher-education organisations that were found to have a lack of cyber-hygiene cognition, knowledge, and skills [41,42].…”
Section: Cyber-hygiene Awareness and Behavioursmentioning
confidence: 99%
“…In India, the study by Rathod [22] indicated a practical need to heighten personal cybersecurity among higher-education students who constantly use distance education through the diversity of cyber-hygiene knowledge, awareness, and behaviours. In UAE, implementing the approaches of cyber-hygiene awareness concern applied as a holistic approach in higher education is critical to affecting online learning practices amid COVID-19 [40]. Other articles from the Arab Region empirically examined cyber-hygiene culture and awareness among students in higher-education organisations that were found to have a lack of cyber-hygiene cognition, knowledge, and skills [41,42].…”
Section: Cyber-hygiene Awareness and Behavioursmentioning
confidence: 99%
“…Although software security is an aspect of quality assurance for all types of software [1], users are still struggling to maintain their information. Regrettably, thousands of software designers and developers are less experienced in security skills as these were not part of their curriculum at university [2]. Different security techniques have been proposed to be applied in each software development life cycle (SDLC) phase, comprising requirements, design, coding, and testing.…”
Section: Introductionmentioning
confidence: 99%
“…Different security techniques have been proposed to be applied in each software development life cycle (SDLC) phase, comprising requirements, design, coding, and testing. However, 32% of research work in the existing literature focused on techniques solely in the design stage [2]. This is because the vulnerabilities of design are the major source of security risk in software systems, and 50% of software errors are often identified in the design stage [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study can assist three types of practitioners: (a) mobile app developers to understand the characteristics and the capability of the studied obfuscators and deobfuscators, (b) researchers and engineers to address the identified drawbacks and enhance the overall health of smartphone ecosystems, and (c) managers of cybersecurity academic programs to embed suitable obfuscation tools in their curricula [9]. This paper is organized as follows.…”
mentioning
confidence: 99%